Interacting Socially with the Internet of Things (IoT): Effects of Source Attribution and Specialization in Human-IoT Interaction - Kim, Ki Joon (Journal of computer-mediated communication, 2016)
This study investigates the theoretical mechanisms by which the variations in source attribution (multiple sources vs. single source) and specialization (multifunctionality vs. single functionality) of Internet of Things (IoT) devices influence the quality of human–IoT interaction. Results from a between‐subjects experiment (N = 100) indicate that IoT devices that elicit the sense of multiple agencies and are specialized in a single function induce greater social presence and perceived expertise, which, in turn, lead individuals to show a more positive attitude toward the devices and to ascribe greater quality to the information transmitted by them. The results also reveal that the effect of multiple source attribution is more pronounced for individuals for whom the content of the information has low personal relevance.